2022
DOI: 10.3390/nu14204341
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet and Female Fertility across Lifespan: A Comparative Lesson from Mammal Models

Abstract: Female reproduction focuses mainly on achieving fully grown follicles and competent oocytes to be successfully fertilized, as well as on nourishing the developing offspring once pregnancy occurs. Current evidence demonstrates that obesity and/or high-fat diet regimes can perturbate these processes, leading to female infertility and transgenerational disorders. Since the mechanisms and reproductive processes involved are not yet fully clarified, the present review is designed as a systematic and comparative sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 250 publications
0
18
1
Order By: Relevance
“…Several studies conducted in mammals have shown that maternal HFD and obesity have negative impacts on fecundity and offspring development (5)(6)(7)(8)(9)(10)(11)(12). Previous studies have proposed that various factors that transmit from dams to fetuses affect offspring development (5,10,11,(18)(19)(20)(21)(22)24,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted in mammals have shown that maternal HFD and obesity have negative impacts on fecundity and offspring development (5)(6)(7)(8)(9)(10)(11)(12). Previous studies have proposed that various factors that transmit from dams to fetuses affect offspring development (5,10,11,(18)(19)(20)(21)(22)24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of maternal diet are thought to be mediated by those constituents (3). For example, previous studies with mammalian models have shown that maternal high-fat diet (HFD) feeding caused not only subfertility in dams (5)(6)(7)(8)(9) but also a higher predisposition toward developmental abnormalities (10)(11)(12) and metabolic diseases (13)(14)(15)(16) in offspring. Those phenomena are often associated with lipotoxicity (5,11,17), mitochondrial dysfunction (18,19), and epigenetic changes (10,20) in oocytes and/or developing embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a risk factor for diabetes, coronary heart disease, cerebrovascular disease, hypertension, hyperlipidemia and other diseases, which plays a role in the pathogenesis of the above diseases, inducing factors, aggravating factors or both [3]. Although the etiology of obesity is complex, dietary factors, especially the consumption of high-fat diet, are the main risk factors for the development of obesity [4]. Long-term intake of high-fat and high-calorie diet will affect the body's normal lipid metabolism, resulting in disorders of fat decomposition, synthesis and storage, leading to abnormal accumulation of body fat.…”
Section: Introductionmentioning
confidence: 99%
“…As summarized in the review by Jurczewska et al [ 8 ], ovulation-dependent female fertility is influenced by several diet-related factors, especially the excessive intake of high-glycemic-index carbohydrates, large amounts of animal protein, saturated fatty acids, and trans fatty acids. It is known that high-fat diet (HFD) regimens negatively impact on several reproductive processes, such as folliculogenesis, oogenesis, and embryo development/implantation, leading to female infertility and transgenerational disorders [ 9 ]. Although our currently fragmentary knowledge limits the full comprehension of the underlying mechanisms, current evidence suggests that the negative impact of HFDs on fertility may be due to a direct action on reproductive somatic and germinal cells and/or to an indirect effect mediated by endocrine, metabolic, and immune signaling [ 9 ].…”
mentioning
confidence: 99%
“…It is known that high-fat diet (HFD) regimens negatively impact on several reproductive processes, such as folliculogenesis, oogenesis, and embryo development/implantation, leading to female infertility and transgenerational disorders [ 9 ]. Although our currently fragmentary knowledge limits the full comprehension of the underlying mechanisms, current evidence suggests that the negative impact of HFDs on fertility may be due to a direct action on reproductive somatic and germinal cells and/or to an indirect effect mediated by endocrine, metabolic, and immune signaling [ 9 ]. The burden of chronic inflammatory diseases, including Crohn’s disease, negatively impact on female reproduction, potentially contributing to irregular menstrual cyclicity, implantation failure, and other negative fertility outcomes [ 10 , 11 ].…”
mentioning
confidence: 99%